2020
DOI: 10.1007/978-3-030-58208-1_4
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of Running Malware Before it Becomes Malicious

Abstract: As more vulnerabilities are being discovered every year[17], malware constantly evolves forcing improvements and updates of security and malware detection mechanisms. Malware is used directly on the attacked systems, thus anti-virus solutions tend to neutralize malware by not letting it launch or even being stored in the system. However, if malware is launched it is important to stop it as soon as the maliciousness of a new process has been detected. Following the results from [8] in this paper we show, that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…During the analysis of findings made in [2] authors found, that most of the memory access patterns they recorded emerged from BEP. These findings lead to another work [3], where authors showed that memory access patterns from BEP can be used to detect malware with an accuracy similar to the one achieved with memory access patterns emerged from after the Entry Point (AEP). In particular, they achieved a classification accuracy of more than 99% when distinguishing between malicious and benign executables with a help of only 9 BEP memory access patterns.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…During the analysis of findings made in [2] authors found, that most of the memory access patterns they recorded emerged from BEP. These findings lead to another work [3], where authors showed that memory access patterns from BEP can be used to detect malware with an accuracy similar to the one achieved with memory access patterns emerged from after the Entry Point (AEP). In particular, they achieved a classification accuracy of more than 99% when distinguishing between malicious and benign executables with a help of only 9 BEP memory access patterns.…”
Section: Introductionmentioning
confidence: 67%
“…This section is dedicated to the description of the methods used in this paper. Our choice of methods is based on findings made in [5], [2] and [3]. We begin with the description of our data collection process.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations